The role of exosomes and exosomal microRNA in diabetic cardiomyopathy - Gao, Shiyu; Dong, Yue; Yan, Chentao; Yu, Tianhao; Cao, Hongbo (Frontiers in Endocrinology, 2024)
Diabetic cardiomyopathy, a formidable cardiovascular complication linked to diabetes, is witnessing a relentless surge in its incidence. Despite extensive research efforts, the primary pathogenic mechanisms underlying this condition remain elusive. Consequently, a critical research imperative lies in identifying a sensitive and dependable marker for early diagnosis and treatment, thereby mitigating the onset and progression of diabetic cardiomyopathy (DCM). Exosomes (EXOs), minute vesicles enclosed within bilayer lipid membranes, have emerged as a fascinating frontier in this quest, capable of transporting a diverse cargo that mirrors the physiological and pathological states of their parent cells. These exosomes play an active role in the intercellular communication network of the cardiovascular system. Within the realm of exosomes, MicroRNA (miRNA) stands as a pivotal molecular player, revealing its profound influence on the progression of DCM. This comprehensive review aims to offer an introductory exploration of exosome structure and function, followed by a detailed examination of the intricate role played by exosome-associated miRNA in diabetic cardiomyopathy. Our ultimate objective is to bolster our comprehension of DCM diagnosis and treatment strategies, thereby facilitating timely intervention and improved outcomes.